2019
DOI: 10.1093/ajcp/aqz113.088
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Lifting Agent ORISE Gel Remnants Histopathologically Mimic Mucin and Malignancy: A Case Series

Abstract: Introduction There were an estimated 18.1 million new cancer cases in 2018, with colon cancer being the third most common worldwide. Colon cancer development is an accumulation of mutations resulting in normal epithelial cells transforming into adenomas and then adenocarcinomas. In certain scenarios, endoscopic interventions have gained considerable momentum over invasive surgery as an alternative to manage early gastrointestinal lesions. New techniques such as endoscopic mucosal resection (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Recent publications have reported similar side-effects ( Table 2 ). In the 3 case examples presented by Cypher et al , it was observed that, after EMR, Orise™ gel remnants led to a histopathologically mucin-like accumulation, but this was eliminated by PAS, PAS-D, and cytokeratin negative staining [ 11 ]. In a case series containing 4 cases published by Westbrook et al , immediately after Orise™ gel injection, a pale, blue-grey, mucin-like appearance was observed on H&E staining, but this accumulation was mucicarmine-positive and PAS, PAS-D, trichrome, and Alcian blue-negative [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported similar side-effects ( Table 2 ). In the 3 case examples presented by Cypher et al , it was observed that, after EMR, Orise™ gel remnants led to a histopathologically mucin-like accumulation, but this was eliminated by PAS, PAS-D, and cytokeratin negative staining [ 11 ]. In a case series containing 4 cases published by Westbrook et al , immediately after Orise™ gel injection, a pale, blue-grey, mucin-like appearance was observed on H&E staining, but this accumulation was mucicarmine-positive and PAS, PAS-D, trichrome, and Alcian blue-negative [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that the amorphous pale acellular ORISE gel can mimic mucin on histologic examination. 2,3 Although Olivas et al 1 indicate that ORISE gel was identified as a procedural artifact in all of their cases without requiring special stains, we strongly recommend that stains for PAS and mucicarmine be considered whenever these histologic findings are encountered so as to avoid a misdiagnosis of mucinous adenocarcinoma. Certain histologic features, including submucosal hemorrhage, which we have witnessed in our practice and have been previously reported, were not identified in this study.…”
mentioning
confidence: 90%
“…However, there is a thought that trainee participation during ERCP might increase the fluoroscopy time, raising a safety concern. 2,3 Moreover, there are no available data regarding the effects of trainee participation on ERCP total procedural and fluoroscopy times. Therefore, we performed a large-scale analysis from a real-world national endoscopic database, Clinical Outcomes Research Initiative (CORI) v. 4 (2009-2014) to determine the impact of trainee involvement on ERCP procedure times.…”
Section: Impact Of Trainee Involvement On the Total Procedural And Fluoroscopy Time During Ercpmentioning
confidence: 99%
“…Awareness of Orise injections performed during the procedure and the visualization of uniform graypink material in the submucosa without associated stromal or inflammatory responses are helpful clues to avoid the diagnostic pitfall. In doubtful cases, a mucin stain such as PAS/D stain will prove useful, as Orise is PAS/D negative in the polypectomy specimen removed immediately after injection [140].…”
Section: Changes Related With Tattoo and Orise Gelmentioning
confidence: 99%